2001
DOI: 10.1007/bf03186072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of W and N addition on the mechanical properties of 10Cr steels

Abstract: The effect of W and N on the creep properties and microstructural degradation in 10Cr steels was studied. Creep testing was performed to determine the creep rupture strength and minimum creep rate. Transmission electron microscopy was used to observe the microstructural degradation during the creep deformation. W and N which were added to the 10Cr steel increased the creep rupture strength and decreased the minimum creep rate. As W and N were added, the thermal stability of the subgrain and carbide was improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It has also been revealed that the thermal stability of nitrides is superior to carbides because the enthalpy of formation of nitrides was higher than that of carbides. [ 36 ] As a result, the pinning effect of the carbonitrides was more obvious in the PN carburized specimen, as shown in Figure 5d,g. The variation in austenite grain size of the case layer in PN carburized specimen was induced by the combined effect of carbon and nitrogen.…”
Section: Resultsmentioning
confidence: 93%
“…It has also been revealed that the thermal stability of nitrides is superior to carbides because the enthalpy of formation of nitrides was higher than that of carbides. [ 36 ] As a result, the pinning effect of the carbonitrides was more obvious in the PN carburized specimen, as shown in Figure 5d,g. The variation in austenite grain size of the case layer in PN carburized specimen was induced by the combined effect of carbon and nitrogen.…”
Section: Resultsmentioning
confidence: 93%
“…The equilibrium mole percent of the precipitates was affected by the addition of W. In addition, the dissolution temperature of the Laves phase increased with W addition. The increasing content of refractory element such as W causes the stabilization of intermetallic compounds or precipitates at higher temperatures [12][13][14]. Due to the stabilizing effect of Laves phase by W addition, its dissolution temperature is increased and that can affect the size of precipitates.…”
Section: Tungstenmentioning
confidence: 99%
“…Nitrides are more stable and less soluble than the corresponding carbide because the enthalpy of formation of nitrides is higher than that of carbides. So an addition of nitrogen contributes to an increase of the creep rupture strength [6].…”
Section: Introductionmentioning
confidence: 99%